Strangulation, domestic abuse and suicide: learning in and through domestic abuse-related death reviews in England and Wales - Munro, Vanessa E. (International review of victimology, 2025)
At international and domestic levels, there is an increasingly well-established evidence base documenting the incidence of non-fatal strangulation or suffocation in intimate partner relationships. While the meaning and significance attributed to this behaviour can be complicated and contested, it is widely acknowledged that the risks involved are substantial. In the context of abusive relationships, it has been recognised as a reliable predictor of increased risk of domestic homicide with new, bespoke non-fatal strangulation or suffocation offences created in England and Wales to improve pathways to prevention, reporting and prosecution. Despite this, research has continued to question the adequacy of existing professional responses in terms of identification, risk assessment and safety planning, as well as understanding of potential links between exposure to strangulation or suffocation and suicidality. This article draws on a detailed analysis of statutory reviews, conducted in England and Wales in certain cases of domestic abuse–related suicide, alongside a series of stakeholder interviews, to explore the incidence and impact of experiencing strangulation or suffocation upon victims. We focus, in particular, on the prevalence and contexts of such experiences; challenges around disclosure and identification; the adequacy of professional risk-assessment and intervention; and understanding of the complex range of physical, cognitive, mental and emotional effects. Documenting the limited consideration often given by agencies and review panels alike to the incidence and impact of non-fatal strangulation or suffocation in these reviews, we highlight, in particular, a lack of attention to its potential to increase risks of suicidality as well as homicide.